The state of neuro-oncology during the COVID-19 pandemic: a worldwide assessment. Issue 1 (20th February 2021) - Mrugala, Maciej M; Ostrom, Quinn T; Pressley, Shelley M; Taylor, Jennie W; Thomas, Alissa A; Wefel, Jeffrey S; Coven, Scott L; Acquaye, Alvina A; Haynes, Chas; Agnihotri, Sameer; Lim, Michael; Peters, Katherine B; et al.
Abstract: Background: It remains unknown how the COVID-19 pandemic has changed neuro-oncology clinical practice, training, and research efforts. Methods: We performed an international survey of practitioners, scientists, and trainees from 21 neuro-oncology organizations across 6 continents, April 24–May 17, 2020. We assessed clinical practice and research environments, institutional preparedness and support, and perceived impact on patients. Results: Of 582 respondents, 258 (45%) were US-based and 314 (55%) international. Ninety-four percent of participants reported changes in their clinical practice. Ninety-five percent of respondents converted at least some practice to telemedicine. Ten percent of practitioners felt the need to see patients in person, specifically because of billing concerns and pressure from their institutions. Sixty-seven percent of practitioners suspended enrollment for at least one clinical trial, including 62% suspending phase III trial enrollments. More than 50% believed neuro-oncology patients were at increased risk for COVID-19. Seventy-one percent of clinicians feared for their own personal safety or that of their families, specifically because of their clinical duties; 20% had inadequate personal protective equipment. While 69% reported increased stress, 44% received no psychosocial support from their institutions. Thirty-seven percent had salary reductions and 63% of researchers temporarily closed their laboratories. However, the pandemic created positive changes in perceived patient satisfaction, communication quality, and technology use to deliver care and mediate interactions with other practitioners. Conclusions: The pandemic has changed treatment schedules and limited investigational treatment options. Institutional lack of support created clinician and researcher anxiety. Communication with patients was satisfactory. We make recommendations to guide clinical and scientific infrastructure moving forward and address the personal challenges of providers and researchers.